LEVELS OF SOME HEAVY METALS IN WATER AND TISSUES OF CHUB MACKEREL (SCOMBER JAPONICUS) COMPARED WITH PHYSICO-CHEMICAL PARAMETERS, SEASONS AND SIZE OF THE FISH - N. Aktan; S. Tekin-Özan (Journal of Animal and Plant Sciences, 2012)
This study was carried out between October 2009 to July 2010 and heavy metals like Ba, As, Co, Cd, Cr, Cu, Fe, Mn, Ni and Zn were determined from water and 60 fish samples (60 in total) from Antalya Bay. Physic-chemical parameter values were also measured in the seawater from catchment area. Analysis of DORM-3 and DOLT-4, reference materials showed good accuracy with the present analytic system. The temperature varied between 17.77 - 27.76ºC; pH between 7.79 - 10.52; dissolved oxygen between 7.28 - 12.83 mg l-1 and salinity between 21.05‰ - 33.84‰. The seasonal variations of heavy metal levels in some tissues of Scomber japonicus were determined. Significant differences (P<0.05) were found in tissues in relation to the seasons. Linear regression analysis and significant associations between the metal levels in tissues and fish size were also determined. The concentrations of heavy metals in water and fish were also compared with acceptable limits given by national and international water quality guidelines. The present study revealed that the metals level in water increased during spring and decreased in autumn. Both positive and negative correlations were observed between metal contents in water and physico-chemical parameters.
Keywords: Heavy metal; Water; Scomber japonicus; Antalya Bay; Turkey